Pattern of disocclusion in patients with complete cleft lip and palate Padrão de desoclusão em indivíduos com fissura lábio-palatina completa - Daniella Andaluza Dias Matos; Marcelo Lucchesi Teixeira; João Henrique Nogueira Pinto; José Fernando Scarelli Lopes; Gisele da Silva Dalben (University of São Paulo, 2006)
OBJECTIVE: to analyze the pattern of disocclusion during excursive mandibular movements and presence or absence of occlusal interferences and occlusal pathologies (gingival recession and abfraction). METHOD: examination of 120 individuals divided into two groups, as follows: Group 1 - 90 patients with complete cleft lip and palate (study group), subdivided into 30 patients with complete left unilateral cleft lip and palate, 30 patients with complete right unilateral cleft lip and palate and 30 patients with complete bilateral cleft lip and palate; Group 2 - 30 individuals without clefts (control group). RESULTS: 58.8% of patients in Group 1 presented unilateral or bilateral canine guidance, 26.6% presented unilateral or bilateral group function and 54.4% presented lateral movements through the posterior teeth. Regarding protrusive movements, 80% presented anterior guidance and 20% presented posterior guidance. In Group 2, 69.6% of individuals presented unilateral or bilateral canine guidance, 43.2% presented unilateral or bilateral group function and only 13.3% presented lateral movements through the posterior teeth; 3.4% presented protrusion through the posterior teeth. CONCLUSIONS: there was no difference in the pattern of disocclusion between subgroups of patients with clefts. Group 2 presented predominance of bilateral group function, whereas Group 1 presented a higher prevalence of posterior guidance during lateral movements. Protrusion occurred primarily through anterior guidance in Group 2 and through the posterior teeth in Group 1. There was high prevalence of occlusal interferences at the molar area for both groups, yet with no correlation with occlusal pathologies (recession and abfraction). OBJETIVO: avaliar o padrão de desoclusão apresentado nos movimentos excursivos mandibulares e a presença ou não de interferências oclusais e patologias relacionadas à oclusão (recessão gengival e abfração). MÉTODO: exame de 120 indivíduos, divididos em 2 grupos: Grupo 1 - 90 pacientes com fissura completa de lábio e palato, subdivididos em 30 pacientes com fissura completa de lábio e palato unilateral esquerda, 30 pacientes com fissura completa de lábio e palato unilateral direita e 30 com fissura completa de lábio e palato bilateral; e Grupo 2 - 30 indivíduos sem fissuras (grupo controle). RESULTADOS: 58,8% do Grupo 1 apresentaram guia canina uni ou bilateralmente, 26,6% apresentaram desoclusão com função em grupo uni ou bilateral e 54,4% realizaram estes movimentos laterais através dos dentes posteriores; 80% dos pacientes do Grupo 1 realizava protrusão pelos dentes anteriores e 20 % pelos posteriores. Para o Grupo 2, guia canina uni ou bilateral foi observada em 69,6% dos indivíduos, 43,2% apresentaram função em grupo uni ou bilateral e somente 13,3% realizaram os movimentos laterais pelos dentes posteriores. Apenas 3,4% dos indivíduos do Grupo 2 apresentaram protrusão pelos dentes posteriores. CONCLUSÕES: não houve diferença estatisticamente significativa no padrão de desoclusão entre os subgrupos de pacientes com fissuras. O Grupo 2 apresentou predominância de função em grupo bilateral, enquanto o Grupo 1 apresentou maior prevalência de guia posterior durante os movimentos laterais. A protrusão ocorreu principalmente por guia anterior no Grupo 2 e pelos dentes posteriores no Grupo 1. Houve alta prevalência de interferências oclusais na região de molares para ambos os grupos, entretanto sem correlação com patologias oclusais (recessão e abfração).